1995
DOI: 10.1002/tea.3660320408
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and validation of a personal form of an instrument for assessing science laboratory classroom environments

Abstract: The research reported in this article makes two distinctive contributions to the field of classroom environment research. First, because existing instruments are unsuitable for science laboratory classes, the Science Laboratory Environment Inventory (SLEI) was developed and validated. Second, a new Personal form of the SLEI (involving a student's perceptions of his or her own role within the class) was developed and validated in conjunction with the conventional Class form (involving a student's perceptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
2
13

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 30 publications
9
84
2
13
Order By: Relevance
“…This result differed from previous international studies which showed that girls tend to be more positive than boys (Fraser et al, 1995;Khine & Fisher, 2003;She & Fisher, 2002). From the perspective of teacher professional development, this is an encouraging result since schooling effectiveness ought not to depend on learner demographic characteristics.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…This result differed from previous international studies which showed that girls tend to be more positive than boys (Fraser et al, 1995;Khine & Fisher, 2003;She & Fisher, 2002). From the perspective of teacher professional development, this is an encouraging result since schooling effectiveness ought not to depend on learner demographic characteristics.…”
Section: Discussioncontrasting
confidence: 91%
“…For example, the effect of student gender is most widely studied in Asia (Fraser, 2002), with the results showing that girls, compared to boys, tend to (a) perceive their learning environments more positively (Fraser, Giddings, & McRobbie, 1995;Khine & Fisher, 2003;She & Fisher, 2002), (b) report higher levels of encouragement and praise (Frumkin, 2006), (c) have more positive perceptions of all five TCBQ factors (Frumkin & Murphy, 2007), and (d) perceive their teachers as providing more encouragement and praise and exhibiting greater understanding and friendlier behaviors (Özay, Kaya, & Sezek, 2004;Yilmaz Tüzün, 2006). In contrast, male students have reported to perceive their teachers as more controlling (Yilmaz Tüzün, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Over the past two decades, the contribution that a rich learning environment makes toward attaining educational goals such as improvement in learning achievements and attitudes towards studies and school has been considered in educational research (Fraser, Giddings, & McRobbie, 1995;Fraser & Tobin, 1991;Perkins, 1992). The term rich learning environment not only includes physical devices, such as experiment kits or computers, but also the teaching technique, the type of activity pupils engage in, and the method of assessment.…”
mentioning
confidence: 99%
“…Further observational research conducting classroom observations (e.g. using the Fraser et al 1995 instrument for assessing the science classroom environments) and multilevel quantitative analyses taking into account the clustered nature of the data and involving more comparison conditions is needed in order to fully address this issue. However, De Corte et al (2004) state that the high degree of ecological validity is defensible and appropriate when looking at evaluating a classroom curriculum-embedded programme.…”
Section: Methodological Considerations and Future Researchmentioning
confidence: 99%